Perkembangan Siswa Berkebutuhan Khusus dan Siswa yang Tidak Biasa serta Implikasinya dalam Proses Belajar dan Pembelajaran - Ririn Amaliah Putri Sarah; Neviyarni S (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to describe students with special needs in order to increase teacher knowledge in dealing with students with special needs based on learning accommodation. In deinclusive education it must be understood that people of different racial or ethnic, religious, disabilities, and children of all umuru must learn and grow in a collective environment and live in the same community. The objectives of learning can also be achieved without encountering significant obstacles. However, there are still many teachers who have not provided guidance or services for their students who are specifically responsible for students with special needs, because each school must improve the quality of their education by implementing this strategy. Teachers should be able to develop the potential of their students so that they can develop optimally. Therefore, a special strategy is needed that can be used by teachers to achieve educational goals.